Peran Script Writer Dalam Menyampaikan Pesan Moral Melalui Film Sabda Rindu - Nugraha, Panji; Eriend, Dion (CV. ITTC INDONESIA, 2024)
This final project is prepared based on the author's experience during the production of a movie entitled